Genetic Engineering for Cereal Crop Yield Improvement and Disease Resistant Breeding - Asaye Demelash Limenie; Mastewal Alehegn (The Scientific World Journal)
Genetic engineering has revolutionized the field of agriculture, providing innovative solutions to enhance crop productivity and resilience against diseases. Among the various crops, cereals hold a pivotal position in global food security, feeding a significant portion of the world population. Genetic engineering, in cereal crop breeding, has opened new avenues for yield improvement and the development of disease-resistant varieties. Growing population and climate change, traditional breeding methods alone are insufficient to meet the increasing demand for food while ensuring sustainability. Genetic engineering offers a precise and efficient approach to introduce desirable traits into cereal crops, thereby improving yield and reducing the impact of diseases. One of the primary objectives of genetic engineering in cereal crops is to enhance yield potential. This can be achieved by modifying genes associated with key traits such as photosynthetic efficiency, stress tolerance, and nutrient use efficiency. For instance, genetic engineering can be used to increase the efficiency of light capture and conversion into biomass, thereby boosting yield. Disease resistance is another critical area where genetic engineering can make a significant impact. Pathogens and pests pose a constant threat to cereal crops, leading to significant yield losses. Genetic engineering techniques allow the introduction of genes encoding resistance to diseases, such as those from wild relatives or from other organisms. Here, evidence shows that the incorporation of Bacillus thuringiensis (Bt) genes into maize has effectively controlled corn borer infestations, reducing the need for chemical pesticides. This not only reduces yield losses but also minimizes the development of pathogen resistance to single-gene interventions.